Looking Back to Move Forward: The Dymaxion Revisited. (2015) - Kennedy, Russell
Abstract: In 1933 and 1934 the visionary architect, designer, engineer and philosopher Robert Buckminster Fuller built three prototypes of a car he named the Dymaxion. Regarded as a ground breaking concept vehicle, the Dymaxion is arguably more relevant today than when it was conceived over eighty years ago. Although plans to manufacture were abandoned by Chrysler in 1933, the Dymaxion Car was considered the most fuel-efficient car of its time using less than half the amount of gasoline than any other car on the road. This was due to its meticulous design based on scientific first principles, power weight ratios and the laws of aerodynamics. The Dymaxion was spacious and easy to maneuver; it offered multi purpose use options with the passenger capacity of a modern people carrier and represented Buckminster Fuller's social responsibility mantra to create more with less. The brand narrative of the Dymaxion tells a story of sustainability and practicality that resonates with today's vehicle consumer market. The adage suggesting that there is reason why a car's windshield is bigger than its rear view mirror and implies that what lies ahead is much more important than anything behind you. Although this life metaphor acknowledges the importance of an occasional glace back this paper emphasises the strategic value of a precognitive, retrospective approach to design.